Manfaat Story Telling dalam Meningkatkan Kemampuan Berbicara Anak Usia Dini - Aprianti, Neli; Ala Purnawati; Siti Nur'aslinda; Hulta Sari (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2023)
The ability to speak is one aspect of language that is important to develop from an early age. Applying the story telling method by giving the story to be read to the child then the teacher can ask again the contents of the story being told to him, the child can also ask questions about the story. This literature review offers a literature review on the benefits of the story telling method in improving children's speaking skills. Literature is taken from Google Scholar, Mendeley and from other selected reference lists. Publication documents used as references are based on the 2014-2021 range. Articles are selected and entered according to specific selection criteria. The review states that applying the story telling method can improve speaking skills in early childhood where the child's vocabulary increases from the stories read to him so that what the child talks about becomes of higher quality, besides that it is easier for children to ask or answer questions and make opponents his speech easily understands what the child means so that the child's speaking ability increases.